Role of biological agents in treatment of rheumatoid arthritis - Law, S; Taylor, P (Elsevier, 2019)
Advances in understanding of the pathophysiology of rheumatoid arthritis with concurrent advances in protein engineering led to the development of biological disease-modifying antirheumatic drugs which have dramatically revolutionized the treatment of this condition. This review article focuses on the role of biological agents currently employed in the treatment of rheumatoid arthritis, as well as novel biological agents in development.